Spindle wave in intracranial pressure signal analysis for patients with traumatic brain injury: A single-center prospective observational cohort study - Zhu, Jun; Shan, Yingchi; Li, Yihua; Liu, Jiaqi; Wu, Xiang; Gao, Guoyi (Frontiers in Physiology, 2023)
Objective: Intracranial pressure (ICP) monitoring is now widely used in patients with traumatic brain injury (TBI). The present study aimed to describe the morphology of the spindle wave during ICP waveform monitoring in TBI patients and to investigate its clinical significance. Methods: We prospectively enrolled patients with closed TBI admitted to the neurosurgery intensive care unit and underwent ICP sensor placement from January 2021 to September 2021. The patient's Glasgow Coma Scale (GCS) score on admission and at discharge and length of stay in hospital were recorded. ICP monitoring data were monitored continuously. The primary endpoint was 6-month Glasgow Outcome Scale Extended (GOSE) score. Patients with ICP spindle waves were assigned to the spindle wave group and those without were assigned to the control group. The correlation between the spindle wave and 6-month GOSE was analyzed. Meanwhile, the mean ICP and two ICP waveform-derived indices, ICP pulse amplitude (AMP) and correlation coefficient between AMP and ICP (RAP) were comparatively analyzed. Results: A total of 60 patients were included, including 41 males and 19 females. There were no statistically significant differences between groups in terms of age (P=0.89), gender composition (P=0.62), and GCS score on admission (P=0.73). Patients with spindle waves tended to have a higher GCS score at discharge (12.75 vs. 10.90, p=0.01), a higher increment in GCS score during hospitalization (ΔGCS, the difference between discharge GCS score and admission GCS score) (4.95 vs. 2.80, p=0.01), and a better 6-month GOSE score (4.90 vs. 3.68, p=0.04) compared with the control group. And the total duration of the spindle wave was positively correlated with 6-month GOSE (r=0.62, P=0.004). Furthermore, the parameters during the presence of the spindle wave, including mean ICP, AMP, and RAP, demonstrated significant decreases compared with the parameters before the occurrence of the spindle wave (all P<0.025). Conclusions: The ICP spindle wave was associated with a better prognosis in TBI patients. Physiological parameters such as ICP, AMP, and RAP were significantly improved when spindle waves occurred, which may explain the enhancement of clinical outcomes. Further studies are needed to investigate the pathophysiological mechanisms behind this waveform.